2003
DOI: 10.1001/archinte.163.13.1549
|View full text |Cite
|
Sign up to set email alerts
|

High-Density vs Low-Density Lipoprotein Cholesterol as the Risk Factor for Coronary Artery Disease and Stroke in Old Age

Abstract: In contrast to high LDL cholesterol level, low HDL cholesterol level is a risk factor for mortality from coronary artery disease and stroke in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 23 publications
12
109
1
4
Order By: Relevance
“…In older persons, a so-called 'reverse metabolic syndrome' is present where low BMI, low diastolic blood pressure, and low TC predict mortality. However, a low HDL remains a risk factor for mortality even in older persons (34), especially for cardiovascular mortality (35). Sattar et al (36) found that the presence of metabolic syndrome in older persons is associated with type 2 diabetes but not with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In older persons, a so-called 'reverse metabolic syndrome' is present where low BMI, low diastolic blood pressure, and low TC predict mortality. However, a low HDL remains a risk factor for mortality even in older persons (34), especially for cardiovascular mortality (35). Sattar et al (36) found that the presence of metabolic syndrome in older persons is associated with type 2 diabetes but not with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy adults were random blood bank donors ranging in age from 18 to 70 years (n ϭ 30). Healthy 90-year-old donors (n ϭ 10) were enrolled in the cohort of the Leiden 85-plus study (21,22), a prospective population-based study of inhabitants of Leiden, The Netherlands. Health was defined as no acute illness, no death within 3 mo after blood sampling, no severe cognitive impairment and a plasma C-reactive protein level below 10 mg/L.…”
Section: Subjectsmentioning
confidence: 99%
“…In the very elderly there is evidence to suggest that high total cholesterol is associated with longevity (Weverling-Rijnsburger et al, 1997). At this age, it has been reported that HDLc and the ratio TC/HDLc are better predictive risk factors for isquemic CVD than TC or LDLc (Corti et al, 1995;Weverling-Rijnsburger, 2003) The mean HDLc concentration was 60.3 Ϯ 7.6 mg/dl, with higher values for the female group (60.5 Ϯ 7.2) than for the male group (58 Ϯ 8.0) (p ϭ 0.49) and with a significant increasing trend with age (p Ͻ 0.05). This is consistent with data reported in the Cardiovascular Health Study (Ettinger et al, 1992).…”
Section: Age Sex and Serum Lipidsmentioning
confidence: 98%